ANALYSIS OF CONSTRUCTIONS OF TORSION SHOCK ABSORBERS DRILLINGCOLUMN OSCILLATION - Moisyshyn, V. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2023)
Designs of shock absorbers of torsional vibrations of the drilling columnare considered. According to the material of the node that perceives vibrations, the following are distinguished: devices with rubber (or other elastic) elements and devices with metal and rubber-metal elements. The design features of nine devices which allowthe vibrationlevel reduction of the rock-destructive tool, were analyzed.